Tubal Flushing Treatment for Unexplained Infertility - Welie, Nienke van; Ludwin, Artur; Martins, Wellington P.; Mijatovic, Velja; Dreyer, Kim (Seminars in Reproductive Medicine, 2020)
Tubal patency testing was initially introduced as a diagnostic test. However, it has been observed that some tubal patency tests also have a therapeutic effect. This therapeutic effect can be influenced by the contrast medium used during tubal flushing. In this review, we discuss current evidence associated with different methods for tubal flushing and their potential impact on reproductive outcomes in women with unexplained infertility. Furthermore, we discuss their diagnostic accuracy, safety, and cost-effectiveness.
Keywords: infertility; tubal flushing; HyCoSy; hysterosalpingography; contrast medium